(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This paper explores the sociopragmatic and stylistic functions of the interpellative second-person pronoun ‘you’ in contemporary media discourse. Far beyond its traditional grammatical role, ‘you’ operates as a rhetorical device that interpellates the reader into the narrative space, constructing a dialogic illusion and transforming the addressee into an active moral or emotional participant. The study examines how ‘you’ functions as a tool of involvement, emotional intensification, and ideological positioning, particularly in journalistic, opinionated, and persuasive genres such as editorials, blog posts, and digital commentaries. Drawing on selected English-language media texts from 2020 to 2025, the paper employs a sociopragmatic lens supported by concepts from Althusserian interpellation theory, critical discourse analysis, and media stylistics. Findings reveal that the pronoun ‘you’ is increasingly used to blur public/private boundaries, simulate interactivity, and project solidarity or confrontation in highly polarized discursive environments. The paper contributes to understanding how linguistic choices shape reader positioning, ideological alignment, and affective resonance in digital media texts.